Aortopexy for the management of paediatric tracheomalacia – the Alder Hey experience. Issue 2 (23rd February 2020) - Williams, S P; Losty, P D; Dhannapuneni, R; Lotto, A; Guerrero, R; Donne, A J
Abstract: Background: Whilst aortopexy is an accepted and established procedure, there remains considerable heterogeneity within the literature, with inconsistencies in both the approach taken and the technique employed. Furthermore, limited data exist on both patient selection and long-term outcomes. This study aimed to report the experience of managing severe tracheomalacia by way of aortopexy in a large UK paediatric centre. Method: A retrospective case note review was conducted. Mean follow up was five years. Results: Twenty-five patients underwent aortopexy for severe tracheomalacia caused by external vascular compression. Acute life-threatening events precipitated investigation in 72 per cent of cases. Twenty-one patients initially presented to ENT services for investigation, which comprised upper airway endoscopy and imaging with computed tomography angiography. Post-operatively, the majority of patients demonstrated complete resolution of symptoms and were discharged from all associated services. Only four patients required a tracheostomy. Conclusion: Aortopexy offers an effective method of treating severe tracheomalacia due to vascular compression.